Pengaruh Problem Based Learning Berbasis Outdoor Study Terhadap Kemampuan Berpikir Kritis Siswa SMA Pada Materi Sistem Pernapasan - Afdillah Afdillah; Nirwana Anas; Syarifah Widya Ulfa (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This research aims to determine the effect of outdoor study-based problem-based learning on high school students' critical thinking abilities on respiratory system material. This research methodology uses quantitative methods with a quasi-experimental type. The research population was class XI high school students with a sample size of 86 students. Data collection techniques were carried out by observation and written tests. Data analysis techniques use descriptive statistics and inferential statistics. The results of the research show that the average critical thinking ability of students in the experimental class taught using the outdoor study-based Problem Based Learning learning model is in the high category and the average critical thinking ability of students in the control class taught using the conventional learning model is low, this is based on the average posttest score from the experimental class, namely 80.22 and the control class, namely 55.95. The results of hypothesis testing using Independent Sample t-test statistics show that there is an influence of the outdoor study-based problem based learning model on the results of students' critical thinking abilities in the material on the human respiratory system Class XI Science SMA Brigjen Katamso 2 Medan.